Fabrication and Sc-Refinement of SiCp/A356 Composites by Vacuum Stirring Casting Method - Fukun Chen; Kuangfei Wang (Journal of Electrical and Computer Engineering)
Aluminum matrix composites reinforced with 10 vol.% SiC particles (SiCp/Al MMCs) were prepared throughthe vacuum stirring method from SiC particles preoxidated at high temperature, followed by posttreatments of remelting and Sc addition treatment. Major problems during vacuum stirring preparation were investigated. Results show that overoxidation of SiC particles may occur during the vacuum stirring process, which causes loss of SiC particles and increases in “impurity pores” after solidification or aggregation of SiC particles, leading to scarcely improved mechanical properties of the prepared SiCp/Al composites. After Sc addition treatment, the α-Al and eutectic Si phases were obviously refined. The composite matrix was strengthened. The result indicates that the maximum tensile strength of 10 vol.% SiCp/A356 composites with Sc addition treatment was 193.5 MPa, which was increased by 43% compared with the matrix alloy. Moreover, a fracture at particles was detected after Sc addition treatment. The stress could be effectively transferred to the SiC particles when the fracture occurred.